Fas Ligand Enhances Apoptosis of Human Lung Cancer Cells Cotreated with RIG-I-like Receptor Agonist and Radiation - Sato, Yoshiaki; Yoshino, Hironori; Tsuruga, Eichi; Kashiwakura, Ikuo (Current Cancer Drug Targets, 2020)
Background: Retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) play key roles in the antiviral response, but recent works show that RLR activation elicits anticancer activity as well, including apoptosis. Previously, we demonstrated that the anticancer activity of the RLR agonist Poly(I:C)-HMW/LyoVec™ [Poly(I:C)-HMW] against human lung cancer cells was enhanced by cotreatment with ionizing radiation (IR). In addition, cotreatment with Poly(I:C)-HMW and IR induced apoptosis in a Fas-independent manner, and increased Fas expression on the cell surface. Objective: The current study investigated the resultant hypothesis that Fas ligand (FasL) may enhance apoptosis in lung cancer cells cotreated with Poly(I:C)-HMW+IR. Methods: FasL was added into culture medium at 24 h following cotreatment with Poly(I:C)- HMW+IR, after upregulation of cell surface Fas expression on human lung cancer cells A549 and H1299 have already been discussed. Results: FasL enhanced the apoptosis of A549 and H1299 cells treated with Poly(I:C)-HMW+IR. Similarly, IR alone - and not Poly(I:C)-HMW - resulted in the upregulation of cell surface Fas expression followed by a high response to FasL-induced apoptosis, thus suggesting that the high sensitivity of cells treated with Poly(I:C)-HMW+IR to FasL-induced apoptosis resulted from the cellular response to IR. Finally, knockdown of Fas by siRNA confirmed that the high response of treated cells to FasL-induced apoptosis is dependent on Fas expression. Conclusion: In summary, the present study indicates that upregulated Fas expression following cotreatment with Poly(I:C)-HMW and IR is responsive to FasL-induced apoptosis, and a combination of RLR agonist, IR, and FasL could be a potential promising cancer therapy.
Keywords: Apoptosis